Digital Marketing Analytics: Enhancing Marketing Management through IT - Nurani; Abd. Rajab; Muhammad Ikbal; Sri Prilmayanti Awaluddin (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
This study aims to analyze the impact of Digital Marketing Analytics (DMA) and information technology (IT) capability on marketing management effectiveness. A mixed methods approach with a Sequential Explanatory design was employed, beginning with a quantitative survey of 100 digital marketing practitioners across various industries in Indonesia, followed by in-depth interviews with seven key informants. Linear regression analysis revealed that DMA (β = 0.462, p < 0.001) and IT capability (β = 0.387, p < 0.001) jointly contribute significantly (R² = 0.581) to marketing effectiveness. Qualitative findings support that companies integrating analytics into their marketing processes tend to be more responsive, efficient, and adaptive to market dynamics. Successful DMA implementation is influenced by human resource readiness, leadership that promotes a data-driven culture, and adequate IT infrastructure. On the other hand, MSMEs face challenges related to digital literacy and limited access to affordable analytics systems. The study underscores the importance of investing in information systems, employee training, and cross-functional integration to drive meaningful digital transformation in marketing strategy.